Sumber Daya Strategis dan Ketidakpastian Lingkungan Untuk Peningkatan Strategi Kompetitif UKM Kecil Sektor Kuliner Pangkalpinang - Luvia Puterima; Alvito Alvito; Meshanda Priscilia; Muhammad Alka Sogih Mawadha; Sari Sapira; Utari Gita Putri; Yona Melisa Lie; Indah Noviyanti (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Pangkalpinang is one of the areas in the Bangka Belitung Islands which has 24,512 Small and Medium Business in June 2022 and continues to grow every year. It is important for Small and Medium Business to improve the culinary sector's competitive strategy in Pangkalpinang, taking into strategic resources and environmental uncertainties that may affect business. Competitive strategy is useful in determining the sustainability of Small and Medium Business in Pangkalpinang. This includes 1) Strategic resources, a) Human resources (HR), b) Raw materials and suppliers, c) Strategic locations, d) Technology and infrastructure. 2) Environmental uncertainty, a) Consumption trends, b) Competition, c) Regulation, d) Economics and costs. The specific objective of this research is how Small and Medium Business of culinary in the city of Pangkalpinang can overcome obstacles to develop their business and develop competitive strategies. The research method that researchers use is a quantitative method by collecting and analyzing data in the form of statistics to answer the questions that researchers formulated and to test hypotheses. We collect data by sharing Google forms to owner of the Small and Medium Business in several areas of Pangkalpinang City. In this study, the results showed that there was no influence between strategic resources and environmental uncertainty on efforts to improve the competitive strategy of Small and Medium Business in the Pangkalpinang culinary sector. The implication of this research for the future is that further studies of the same kind can be carried out but in different locations to see whether the results of this study will give the same results elsewhere.